2019
DOI: 10.4269/ajtmh.19-0095
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Clinical Infections of Leishmania Imported into Australia: Revising Speciation with Polymerase Chain Reaction-RFLP of the Kinetoplast Maxicircle

Abstract: Leishmaniasis is a vector-borne disease caused by protozoan parasites of the Leishmania genus. In Australia, leishmaniasis is an imported disease that is presenting itself at increased rates because of international travel, the influx of immigrants, and deployment of military operations to endemic regions. Although Leishmania species are morphologically indistinguishable, there is a strong correlation between some causative species of leishmaniasis and the subsequent response to the treatments available and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…The banding pattern produced can be used to identify a particular species, depending on the presence or absence of a restriction enzyme site in the PCR product derived from the target [ 226 ]. It is a relatively inexpensive technique compared to real-time PCR, and a multitude of gene targets can be utilised, including heat-shock protein 70, glycoprotein 63, kDNA, cysteine protease B, mini-exon or NADH dehydrogenase subunit 7 [ 121 , 227 231 ].…”
Section: Methods For the Identification Of Species Of Leish...mentioning
confidence: 99%
See 3 more Smart Citations
“…The banding pattern produced can be used to identify a particular species, depending on the presence or absence of a restriction enzyme site in the PCR product derived from the target [ 226 ]. It is a relatively inexpensive technique compared to real-time PCR, and a multitude of gene targets can be utilised, including heat-shock protein 70, glycoprotein 63, kDNA, cysteine protease B, mini-exon or NADH dehydrogenase subunit 7 [ 121 , 227 231 ].…”
Section: Methods For the Identification Of Species Of Leish...mentioning
confidence: 99%
“…An ITS1-RFLP reported by Schönian et al [ 231 ] was able to differentiate most Leishmania species but was less useful for those species within the L. braziliensis complex [ 232 , 233 ]. Such findings can be problematic, as the clinical presentation of the MCL tropism is caused by more than one of these species, but the response to treatment differs between them [ 129 ].…”
Section: Methods For the Identification Of Species Of Leish...mentioning
confidence: 99%
See 2 more Smart Citations
“…selected genes, all coding regions) could be used as genetic markers to identify Leishmania species and strains and to depict phylogenetic relatedness [ 59 – 62 ]. For example, Kaufer et al used a variation on the Leishmania maxicircle sequences ( ND7 gene) to design PCR–RFLP assays to discriminate nine Leishmania species [ 63 ]. A recent study identified the origin of the intra-species L. donovani hybrid from Himachal Pradesh, India, that was derived from two independent L. donovani parents of the ISC1-Yeti clade from the Nepalese highlands using maxicircle phylogenetics, suggesting the usefulness for examination of intra-species diversity [ 64 ].…”
Section: Discussionmentioning
confidence: 99%